The regulatory effect of chitooligosaccharides on islet inflammation in T2D individuals after islet cell transplantation: the mechanism behind Candida albicans abundance and macrophage polarization - Yayu Zhang; Xiaoguo Ji; Kunlin Chang; Hao Yin; Mengyao Zhao; Liming Zhao (Gut Microbes)
Islet cell transplantation (ICT) represents a promising therapeutic approach for addressing diabetes mellitus. However, the islet inflammation during transplantation significantly reduces the surgical outcome rate, which is related to the polarization of macrophages. Chitooligosaccharides (COS) was previously reported which could modulate the immune system, alleviate inflammation, regulate gut microecology, and repair the intestinal barrier. Therefore, we hypothesized COS could relieve pancreatic inflammation by regulating macrophage polarization and gut microbiota. First, 18S rDNA gene sequencing was performed on fecal samples from the ICT population, showing abnormally increased amount of Candida albicans, possibly causing pancreatic inflammation. Functional oligosaccharides responsible for regulating macrophage polarization and inhibiting the growth of Candida albicans were screened. Afterwards, human flora-associated T2D (HMA-T2D) mouse models of gut microbiota were established, and the ability of the selected oligosaccharides were validated in vivo to alleviate inflammation and regulate gut microbiota. The results indicated that ICT significantly decreased the alpha diversity of gut fungal, altered fungal community structures, and increased Candida albicans abundance. Moreover, Candida albicans promoted M1 macrophage polarization, leading to islet inflammation. COS inhibited Candida albicans growth, suppressed the MyD88-NF-κB pathway, activated STAT6, inhibited M1, and promoted M2 macrophage polarization. Furthermore, COS-treated HMA-T2D mice displayed lower M1 macrophage differentiation and higher M2 macrophage numbers. Additionally, COS also enhanced ZO-1 and Occludin mRNA expression, reduced Candida albicans abundance, and balanced gut microecology. This study illustrated that COS modulated macrophage polarization via the MyD88/NF-κB and STAT6 pathways, repaired the intestinal barrier, and reduced Candida albicans abundance to alleviate islet inflammation.